La Constitution canadienne et la protection des minorités ethniques - Woehrling, José (Les Cahiers de droit, 1986)
Canada's international obligations for protecting minorities imply non discrimination and the establishment of means for allowing minorities to preserve and perpetuate their national characteristics. The author deals with the scope and role of the Canadian Charter in recognizing the value of « multiculturalism. » He presents the various obstacles that lay in the way of exercising the right to multiculturalism such as the financial cost for achieving it and the principle of « territoriality. »